Penerapan Model Pembelajaran PBL dengan Pendekatan Etnosains terhadap Keterampilan Berpikir Kritis dan Kolaboratif Peserta Didik di Kelas 4 Sekolah Dasar pada Materi Bagian Tubuh Tumbuhan - Rini Puspita Sari; Nadia Aldyza; Syifa Saputra (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the effect of implementing an Ethnoscence-based Problem Based Learning (PBL) model on improving the critical thinking and collaborative skills of fourth-grade students at SD Negeri Sungai Iyu on the topic of plant body parts. The research background is based on low student engagement, suboptimal critical thinking and collaboration skills, and the less-than-maximal implementation of contextual learning. The research method employed a Quasi-Experimental design of the Nonequivalent Control Group Design type. Data were collected through tests, observations, interviews, and questionnaires involving a sample of 32 students. The results indicate: (1) A significant improvement in critical thinking skills, with the average score increasing from 66.56 (31% mastery) to 79.53 (84% mastery). This is supported by a paired t-test (p=0.000) and regression analysis (Multiple-R = 0.871), indicating that the model explains 75.9% of the variation in improvement. (2) A highly positive improvement in collaborative skills, demonstrated by an increase in the average score from 26.63 (pretest) to 31.81 (posttest), with mastery reaching 84%. Significant test results (p=0.000) and regression analysis show a very strong relationship strength (Multiple R = 0.871). Observations and interviews illustrate that the PBL framework within a project to diagnose banana tree diseases fostered natural interaction, discussion, and role-sharing. (3) Student responses were highly positive; students were actively engaged and able to construct arguments based on a synthesis of scientific observations and local wisdom (ethnoscience), such as consulting with local farmers. The integration of PBL and ethnoscience effectively enhanced active engagement, appreciation for the relevance of science, and critical thinking and collaborative skills.